The History of King Richard the Third. - Logan, Goerge W. (Indiana University Press, 2005)
This book is Thomas More's masterpiece. With the help of Shakespeare, whose Richard the Third took More's work as its principal model, the History determined the historical reputation of an English king and spawned a seemingly endless controversy about the justness of that reputation. Logan has produced a scholarly yet accessible edition designed to make More's exhilarating work fully accessible to modern readers. The text is preceded by a general introduction, a chronology, and suggestions for further reading. An appendix reprints passages from key sources and analogues, enabling the reade.